Somatic comorbidities and health related uncertainty among Swedish adolescents with ADHD - Lundqvist, Sara; Röjås, Sara; Bador, Kourosh; Råstam, Maria; Kerekes, Nóra (Frontiers in Psychiatry, 2025)
IntroductionAttention-deficit/hyperactivity disorder (ADHD) frequently exists alongside psychiatric comorbidities. The coexistence of somatic diseases and ADHD constitutes a growing field of research.MethodThis study aimed to examine the prevalence of common somatic diseases in adolescents with ADHD and compare them with those in adolescents without any psychiatric diagnoses. A cross-sectional study was conducted among a convenient sample of Swedish upper secondary school students aged 15 to 19 years. Data were collected using an electronic version of the “Mental and Somatic Health without borders” survey. In 2020, 1608 adolescents completed the survey and provided self-reports of their psychiatric and somatic diagnoses.ResultsAmong the sample of Swedish adolescents, 5.5% reported having ADHD diagnoses. These adolescents reported more somatic comorbidities than those without any psychiatric diagnosis (comparison group). The most common somatic comorbidities among those with ADHD were allergies (43.4%), asthma (24.7%), and skin diseases (16.7%), which prevalences were significantly higher than those reported by adolescents in the comparison group. However the effect sizes of these differences were negligible (allergies: p=0.002, Cramer’s V=0.08; asthma: p=0.041, Cramer’s V=0.06; skin diseases: p=0.007, Cramer’s V=0.08), raising questions about the practical implications of these findings. Allergies were significantly more common in both genders with ADHD (p=0.038, Cramer’s V=0.08 in women and p=0.038, Cramer’s V=0.09 in men). Additionally, men with ADHD showed a significant association with skin diseases (p=0.007, Cramer’s V=0.12) while women with ADHD were significantly more likely to have migraine (p=0.038, Cramer’s V=0.08). Notably, adolescents with ADHD reported significantly higher rates of uncertainty regarding the existence of diabetes, rheumatoid diseases, asthma (with negligible effect sizes), and thyroid diseases (with a small effect size) than those without any psychiatric diagnoses, suggesting heightened health related anxiety within this group.ConclusionsAdolescents with ADHD reported more somatic comorbidities and greater uncertainty about the potential presence of additional somatic conditions compared to adolescents without psychiatric diagnoses. These findings highlight the importance of addressing both health literacy and access to healthcare. By focusing on this group, we cannot only improve their ability to understand and navigate the healthcare system but also strengthen their confidence in managing their own health.